Origin verification of imported infant formula and fresh milk into China using stable isotope and elemental chemometrics. (October 2021) - Zhou, Xiuwen; Yan, Zhi; Jin, Baohui; Wu, Yingying; Xie, Liqi; Chen, Haiquan; Lin, Guanghui; Zhao, Yan; Rogers, Karyne M.; Wu, Hao
Abstract: China is the largest importer of infant formula. However, monitoring the authenticity of infant formula has long been a problem in China. The origin of infant formula is more difficult to trace than fresh milk because it contains many foreign additives that cannot be correlated to a specific country. In this study, stable isotope ratios ( δ 15 N, δ 13 C, δ 34 S, δ 2 H and δ 18 O) of bulk infant formula milk powder and fresh milk from 6 origins (Netherlands, Switzerland, France, Denmark, New Zealand and China) were compared to establish geographical origin isotopic characteristics. N, C and S elemental contents were also investigated to improve origin verification. Artificial Neural Network (ANN) and Linear Discriminant Analysis (LDA) were used to establish origin verification models of imported infant formula and fresh milk. Overall, results showed that infant formula had higher δ 18 O, δ 2 H, δ 15 N and δ 34 S values, and lower δ 13 C values than fresh milk. δ 18 O and δ 2 H values of infant formula varied more than in fresh milk, as the additives are not necessarily sourced from the same country, while δ 15 N, δ 13 C and δ 34 S values were more negative, most likely due to the presence of numerous additives probably from non-dairy sources such as fats, sugars, amino acids and proteins. This study showed a combination of isotopes and elemental contents could completely discriminate the origin of infant formula imported into China, with a discrimination accuracy of 100% using ANN. Highlights: Isotopes and elements of infant formula and fresh milk from 6 origins were compared. Fresh milk N, C and S isotopes had a wider range of values than infant formula. Infant formula H isotopes had a wider range than fresh milk. High predictive origin ability for infant formula was achieved using ANN.